Peningkatan Minat Belajar IPAS Melalui Pendekatan Deep Learning Berbasis Proyek di Sekolah Dasar - Novia Ismaylani Herninda; Muhaiminah Jalal; Nisa Aulia (Kartika: Jurnal Studi Keislaman, 2026)
This study was motivated by the low level of student interest in the Natural and Social Sciences (IPAS) subject in Class VB at SD Negeri 131/IV in Jambi City. This low level of interest was evident in the students’ lack of attention, engagement, and enthusiasm during the learning process. The purpose of this study was to increase student interest through the implementation of a project-based Deep Learning approach. The method used was Classroom Action Research (CAR) based on the Kemmis and McTaggart model, conducted in two cycles. The research subjects consisted of 35 students in Grade VB. Data collection techniques included observation, questionnaires, and documentation, while data analysis used quantitative descriptive techniques. The results of the study indicate that the implementation of a project-based Deep Learning approach can increase students’ interest in learning. In the pre-cycle stage, the average student learning interest was 48.8% with a mastery rate of 28.5% (10 students). In Cycle I, it increased to 75.7% with a mastery rate of 72.2% (26 students), and in Cycle II, it increased to 95.3% with a mastery rate of 100% (35 students). Teacher activity also increased from 75% in Cycle I to 100% in Cycle II. Thus, the project-based Deep Learning approach proved effective in increasing students’ interest in learning IPAS in elementary school